Functional biological pacemaker generation by T-Box18 protein expression via stem cell and viral delivery approaches in a murine model of complete heart block. (March 2019) - Gorabi, Armita Mahdavi; Hajighasemi, Saeideh; Khori, Vahid; Soleimani, Masoud; Rajaei, Maryam; Rabbani, Shahram; Atashi, Amir; Ghiaseddin, Ali; Saeid, Ali Kazemi; Ahmadi Tafti, Hossein; Sahebkar, Amirhossein
Graphical abstract: Abstract: Despite recent advances in the treatment of cardiac arrhythmia, the available options are still limited and associated with some complications. Induction of biological pacemakers via Tbx18 gene insertion in the heart tissue has been suggested as a promising therapeutic strategy for cardiac arrhythmia. Following a previous in vitro study reporting the production of Tbx18-expressing human induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs), we aimed to investigate the efficacy of these engineered cells to generate pacemaker rhythms in a murine model of complete heart block. We also attempted to generate a functional pacemaker by Tbx18 overexpression in native cardiac cells of rat heart. The hiPSC-derived pacemaker cells were produced by lentiviral delivery of Tbx18 gene to stem cells during a small molecule-based differentiation process. In the present study, 16 male albino Wistar rats were randomly assigned to Tbx18-lentivirus (n = 4) and Tbx18-pacemaker cells (n = 4) administered via injection into the left ventricular anterolateral wall. The control rats received GFP-lentiviruses (n = 4) and GFP-pacemaker cells (n = 4). Fourteen days after the injection, the rats were sacrificed and analyzed by electrocardiography (ECG) recording using a Langendorff-perfused heart model following complete heart block induced by hypokalemia and crashing. Immunofluorescence staining was used to investigate the expression of Tbx18, HCN4 and connexin 43 (Cx43) proteins in Tbx18-delivered cells of heart tissues. The heart rate was significantly reduced after complete heart block in all of the experimental rats (P < 0.05). Heart beating in the Tbx18-transduced hearts was slower compared with rats receiving Tbx18-pacemaker cells (P = 0.04). The duration of ventricular fibrillation (VF) was higher in the lentiviral Tbx18 group compared with the GFP-injected controls (P = 0.02) and the Tbx18-pacemaker cell group (P = 0.02). The ECG recording data showed spontaneous pacemaker rhythms in both intervention groups with signal propagation in Tbx18-transduced ventricles. Immunostaining results confirmed the overexpression of HCN4 and downregulation of Cx43 as a result of the expression of the Tbx18 gene and spontaneously contracting myocyte formation. We confirmed the formation of a functional pacemaker after introduction of Tbx18 via cell and gene therapy strategies. Although the pacemaker activity was better in gene-received hearts since there were longer VF duration and signal propagation from the injection site, more data should be gathered from the long-term activity of such pacemakers in different hosts.